Digital entrepreneurship - Allen, Jonathan P. (New York : Routledge, 2019)
Technology has enabled a new age of entrepreneurship as entrepreneurs find digital tools that enable new ventures to exploit commercial opportunities around the world. This textbook provides students with expert guidance on using technology platforms to start new ventures. With an award-winning approach, the author guides readers through the process of a lean startup, taking a "digital first" approach to entrepreneurship. Students using the book will emerge with enhanced understanding of different digital business models, analytical skills for digital ventures, and the confidence to move from prototype to product. Online resources such as slides, a sample syllabus, and exercises encourage the classroom to become an interactive and dynamic space. To access these resources, please visit https://www.learndigitalentrepreneurship.com
Cover; Half Title; Title; Copyright; Contents; Preface: Entrepreneurship in a Digital World; 1 Digital Entrepreneurship: New Opportunities and Challenges; 2 Choosing a Digital Business Idea; 3 Creating a Digital Business Design; 4 Building a Business Prototype; 5 Digital Content for Business; 6 Business Prototype Look and Feel; 7 Business Prototype Features; 8 Web Analytics; 9 Creating and Tracking Business Goals; 10 Usability and Customer Experience; 11 Customer Acquisition in a Digital World; 12 Digital Business Experiments; 13 Launching a New Digital Business Venture; Key Terms; Appendices
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Information technology -- Economic aspects; Entrepreneurship; Internet service providers; New business enterprises; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Entrepreneurship